AKTUALISASI MEDIA WHATSAPP DALAM PEMBELAJARAN DI SMP NEGERI SELANGIT - Ahmad Taufik; Maemunah Maemunah; Siti Hana; Heti Salama (LP3M IAI Al Urwatul Wutsqo Jombang, 2022)
When you can carry out a lesson in order to implement a curriculum plan (directly program) the standard of the learning process, with the involvement of students and teachers that occurs in the school environment. Online learning of Islamic religious education (PAI) WhatsApp group is a learning that can take place in a network where teacher turmoil and how to provide teaching materials do not meet face-to-face. WhatsApp group online learning is a learning process when schools can apply emphasis on character building from various personalities of students, both intrapersonal and interpersonal characters. From the background of the research, the author can formulate a problem formulation, namely the implementation of PAI online learning based on soft skills, the effectiveness of PAI online learning through WhatsApp groups, controlling PAI online learning through WhatsApp groups, and evaluative online learning through WhatsApp groups. The purpose of this study is to describe the implementation of PAI online learning through the whatsapp group, planning PAI online learning through the whatsapp group, controlling PAI online learning through the whatsapp group, and evaluative online learning through the whatsapp group.